Transcatheter Patent Ductus Arteriosus (PDA) Device Closure: Comparative Outcomes Between Conventional Versus Single Vessel Approach - Akbar, Hajira (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine post procedural outcomes, complications, and effectiveness of transcatheter PDA closure using single-vessel and Conventional Arteriovenous access in pediatric patients. Study Design: Analytical Cross-Sectional. Place and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases (AFIC/NIHD), Rawalpindi, Pakistan; January 2024- December 2025. Methodology: The study included 269 children with isolated PDA (<12 years, <30 kg) were enrolled. Data were collected retrospectively and prospectively from patients of transcatheter PDA closure. Children with other associated congenital cardiac anomalies, pulmonary hypertension, or PDA-dependent cardiac defects were excluded from the study. Participants were divided into two groups; A and B, where Group A had single vessels and Group B had the conventional arteriovenous approach. Device closures were performed and all metrics pertaining to the procedures, the complications, and the outcomes post procedure were documented. Results: Transcatheter PDA closure was performed in 269 children using a single vessel approach (Simple Vessel Approach (n=145) and conventional arteriovenous approach (n=124). Baseline age, weight, and PDA size were similar across groups. Fluoroscopy time and contrast volume did not differ significantly. Compression time was longest with femoral arterial access and shortest with the arteriovenous approach, and anticoagulation strategies varied by access route (p<0.001). Most patients were discharged on the first post-procedure day. In-hospital mortality was low (1.5%), and the majority had no complications. Conclusion: Single vessel approach appears safe and feasible alternatives to conventional arteriovenous access for pediatric PDA closure, with low in-hospital complication rates. Access route selection was significantly associated with device choice.